Gentle Nazarene or Failure?: Buddhist Perspectives on Jesus in Colonial and Post‐colonial Contexts - Harris, Elizabeth J. (The ecumenical review, 2020)
This paper argues through three case studies that representations of Jesus by practitioners of other religious traditions, in this case Buddhists, are conditioned by historical and social factors. The first two cases, David Hewavitarne/Anagārika Dharmapāla (1864-1933) and Allan Bennett/Ananda Metteyya (1872-1923), demonstrate that negative experience of Christian theology and practice broadly resulted in the judgment that Jesus was a failure. The more conciliatory and exploratory approach of my third case study, convert to Buddhism Maurice O'Connell Walshe (1911-1998), illustrates the factors that have led to (1) socially engaged cooperation between Buddhists and Christians and (2) the respectful dialogue on Jesus and the Buddha in the 21st century.